2023
DOI: 10.1186/s12866-023-02836-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences in the gut microbiome of bats using terrestrial vs. aquatic feeding resources

Abstract: Bat gut microbiomes are adapted to the specific diets of their hosts. Despite diet variation has been associated with differences in bat microbiome diversity, the influence of diet on microbial community assembly have not been fully elucidated. In the present study, we used available data on bat gut microbiome to characterize the microbial community assembly of five selected bat species (i.e., Miniopterus schreibersii, Myotis capaccinii, Myotis myotis, Myotis pilosus, and Myotis vivesi), using network analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…According to the principal component analysis, the diversity of predicted functional pathways in the gut microbiota of N. noctula and V. murinus showed more similarities compared to C. perspicillata. As expected, these results demonstrate that gut microbiota features, including microbial metabolism, strongly depend on bat diet [56,57]. The RA of predicted functional pathways in the gut microbiota of studied bats is in with previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…According to the principal component analysis, the diversity of predicted functional pathways in the gut microbiota of N. noctula and V. murinus showed more similarities compared to C. perspicillata. As expected, these results demonstrate that gut microbiota features, including microbial metabolism, strongly depend on bat diet [56,57]. The RA of predicted functional pathways in the gut microbiota of studied bats is in with previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Available tools such as PICRUSt, PICRUSt2, Tax4Fun, and FaproTax can be used to infer microbial functional genes from 16S rRNA amplicon sequencing data (Douglas et al, 2020;Sun et al, 2020). In particular, PICRUSt2 has been applied to elucidate the functional profiles of microbiota from various animals (Wu-Chuang et al, 2022a;Azělytėet al, 2023;Corduneanu et al, 2023), including several tick species such as I. scapularis (Wu-Chuang et al, 2022b), I. ricinus (Mateos-Hernańdez et al, 2020;Mateos-Hernańdez et al, 2021), Amblyomma variegatum, Amblyomma hebraeum, and Hyalomma truncatum (Chigwada et al, 2022). Predicted metabolic profile analysis using PICRUSt2 revealed a high functional redundancy in the tick microbiota (Estrada-Peña et al, 2020).…”
Section: The Epistemological Challengementioning
confidence: 99%
“…In addition to these morphological and physiological adaptations, recent research has suggested that the gut microbiota of bats may also play a role in their feeding habits [ 6 ]. The gut microbiota comprises a complex assemblage of microorganisms residing in the digestive tracts of animals, including bats.…”
Section: Introductionmentioning
confidence: 99%